Prenatal Methamphetamine Exposure and Adverse Neonatal Outcomes: A Nationwide Cohort Study - Gabrhelík, Roman; Skurtveit, Svetlana; Nechanská, Blanka; Handal, Marte; Mahic, Milada; Mravčík, Viktor (European addiction research, 2021)
BACKGROUND: There is limited knowledge on the adverse outcomes in newborns after maternal methamphetamine (MA) use during pregnancy. OBJECTIVES: To compare neonatal outcomes in newborns exposed to MA with the newborns of opioid-exposed mothers and of mothers from the general population (GP). METHOD: A cohort study using nationwide registries in Czechia (2000-2014). Women hospitalized with a main diagnosis of MA use disorder during pregnancy (n = 258) and their newborns were defined as MA-exposed. The comparison groups consisted of women (n = 199) diagnosed with opioid use disorder during pregnancy, defined as opioid-exposed, and women (n = 1,511,310) with no substance use disorder diagnosis (GP). The neonatal outcomes studied were growth parameters, gestational age, preterm birth, and Apgar score. To explore the associations between MA exposure and neonatal outcomes, regression coefficients (b) and odds ratios from multivariable linear and binary logistic regression were estimated. RESULTS: MA-exposed women had similar socio-economic characteristics to opioid-exposed, both of which were worse than in the GP. After adjustment, MA exposure was associated with a more favourable birthweight when compared to the opioid-exposed (adjusted mean differences [aMD] b = 122.3 g, 95% CI: 26.0-218.5) and length (aMD b = 0.6 cm, 0.0-1.1). Unadjusted results from the comparison with the GP showed that the MA group had poorer neonatal outcomes, especially in the growth parameters. Adjustment for background characteristics had a profound effect on the comparison with the GP. After adjustment, MA exposure was associated only with a slightly reduced birthweight (aMD b = -63.0 g, -123.0 to -3.1) and birth length (aMD b = -0.3 cm, -0.6 to 0.0). CONCLUSIONS: Although the observed negative outcomes were large in the MA-exposed newborns, the adjustment had a profound effect on the comparison with the GP, indicating the large influence of lifestyle and socio-economic factors in these high-risk pregnancies. MA-exposed newborns had better neonatal outcomes compared to opioids-exposed.
Keywords: novorozenec; Infant, Newborn; výsledek těhotenství; Pregnancy; Humans; zpožděný efekt prenatální expozice; Prenatal exposure; Premature Birth; kohortové studie; Female; Pregnancy Outcome; lidé; Pregnancy Complications; Opioids; Health registries; methamfetamin; Cohort Studies; ženské pohlaví; těhotenství; Czech Republic; komplikace těhotenství; Prenatal Exposure Delayed Effects; Česká republika; předčasný porod; Neonatal outcomes; Methamphetamine